Cellulite, overweight and obesity in female patients with hypothyroidism - Ewelina Szkutnicka; Marzena Samardakiewicz; Bartłomiej Drop; Agnieszka Barańska; Anna Sokołowska; Hubert Szkutnicki; Iwona Chmiel-Perzyńska (Kazimierz Wielki University, 2018)
Introduction. A bad diet and lack of physical activity are the most commonly reported causes of overweight and cellulite. Unfortunately, problems with slimming and "orange peel" may not only result from dietary mistakes but also hormonal imbalance. Aim of the paper. The aim of the study was to assess the impact of hypothyroidism on overweight, the degree of obesity and the prevalence of cellulite in patients with hypothyroidism in the course of Hashimoto's disease. Material and methods. The study was carried out in March 2018 in Opole Lubelskie. The study group consisted of 35 women over 18 years of age. The research tool was the standardised Contour Drawing Rating Scale (Thompson and Gray) and the author's questionnaire. Results. The calculated BMI values of the subjects showed the presence of overweight in every fifth woman, class I obesity in 11.43%, class II obesity in 28.57% and class III obesity in 40% of the respondents. According to 94.28% of the respondents, physical activity affects the appearance of the body, but only 5.72% of the study subjects do sports. Among the respondents, over half (68.57%) indicated the presence of third-degree cellulite. Conclusions. Cellulite is most common in overweight and obese women. The occurrence of overweight and obesity may be associated with a poor diet and low physical activity, but also with hormonal disorders resulting from thyroid dysfunction.